Clinical characteristics and relationship between myasthenia gravis and premature ovarian failure: report of two cases - Liming Cao; Weibin Liu; Zhishan Zhu (Journal of International Medical Research, 2019)
Myasthenia gravis (MG) and premature ovarian failure (POF) are rare. MF and POF greatly affect patients’ health. Combined occurrence of MF and POF in young women can have serious consequences. We report two cases of MG with POF. Case 1 was a 20-year-old woman who presented with myasthenic crisis and menopause in September 2015 and November 2015, respectively. The patient’s estradiol and follicle-stimulating hormone levels were abnormal. She was administered plasmapheresis and methylprednisolone pulse therapy. She improved and was discharged with normal restoration of menstruation after 3 months. Case 2 was a 21-year-old woman who had right eyelid droop and double vision in June 2014. She presented with menstrual disorder and menopause in August 2014 and September 2014, respectively. Estradiol and follicle-stimulating hormone levels were abnormal. She underwent progesterone therapy. She was admitted to hospital again in March 2016 with a myasthenic crisis. She received methylprednisolone pulse therapy and underwent thymectomy, but menstruation was not restored. In conclusion, there is comorbidity of POF in MG, and there is a close relationship between these two diseases. MG may subsequently lead to development of POF, and timely immunotherapy for MG may normalize POF.